2017
DOI: 10.5937/zasmat1702189r
|View full text |Cite
|
Sign up to set email alerts
|

Production of rubber plasticizers based on waste PET: Techno-economical aspect

Abstract: Production of rubber plasticizers, based on waste poly(ethylene terephthalate) (PET), and economic effectiveness of developed technologies are presented and discussed. Waste PET glycolyzates, named diisononyl terephthalate(DINTP), didecyl terephthalate (DDTP), dibenzyl terephthalate(DBTP) and diglyceryl terephthalate(DGTP), were obtained by catalytic depolymerization of PET with isononyl alcohol, decyl alcohol, benzyl alcohol and glycerol. The structural analysis of the synthesized plasticizers was done using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, studies have demonstrated that the use of diethylene glycol terephthalate modified with maleic anhydride results in a material with commendable mechanical properties [30]. Terephthalate-based plasticizers contribute to excellent product durability, flexibility at low temperatures, and enhanced electrical insulation capabilities [32]; thus, they hold promise as a viable and beneficial alternative. Therefore, if waste PET, a polyester-type thermoplastic polymer, and reactants of natural origin are used in plasticizer syntheses, an extraordinary situation is realized that includes the principles of green chemistry in technological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that the use of diethylene glycol terephthalate modified with maleic anhydride results in a material with commendable mechanical properties [30]. Terephthalate-based plasticizers contribute to excellent product durability, flexibility at low temperatures, and enhanced electrical insulation capabilities [32]; thus, they hold promise as a viable and beneficial alternative. Therefore, if waste PET, a polyester-type thermoplastic polymer, and reactants of natural origin are used in plasticizer syntheses, an extraordinary situation is realized that includes the principles of green chemistry in technological processes.…”
Section: Introductionmentioning
confidence: 99%
“…A new engineering approach to developing automotive tires, or the concept of green tires, adopted recently, requires continuous growth in terms of better fuel economy consumption, reduction of harmful gas emissions, improved driving safety, and increased product durability [1]. This work aimed to use styrene butadiene rubber (SBR) and butadienenitrile (NBR) as a network precursor in rubber blends with tetramethyl thiuram disulfide (TMTD) and tetramethyl thiuram monosulfide (TMTS) as accelerators and environmentally friendly plasticizers obtained from PET recycling to get nanocomposite materials with adequate properties [2]. The influence of synthesized accelerators and plasticizers on blend characteristics as well as the dynamic-mechanical and mechanical properties of the obtained elastomer nanocomposites will be examined and compared.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, PET-based eco-resins will be obtained by PET depolymerization with various poly-hydroxyl alcohols/glycols and amines. These hydroxyl/amino-terminated products (monomeric or oligomeric products, liquid to highly viscous) can be further functionalized to obtain various products, such as plasticizers for rubber blends [2,4]. In rubber production, plasticizers are generally used to help the movability of polymeric chains, enhance rubber processability, and improve its physico-mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical recycling of PET trash can greatly decrease environmental difficulties caused by incineration or landfill accumulation of this material. It can be reused in the production of new products such as polyester, epoxy, and alkyd resins [15], and plasticizers [16]. Primary (Pre-Consumer Industrial Scrap), secondary (Mechanical Recycling), tertiary (Chemical Recycling), and quaternary (Energy Recovery) waste PET recycling is possible [17].…”
Section: Introductionmentioning
confidence: 99%